Assessment of radiation knowledge among medical personnel in nuclear emergency preparedness: a cross-sectional study - Xie, Yanjun; Wang, Xining; Lan, Yuemin; Xu, Xinyu; Shi, Shaoteng; Yang, Zhihao; Li, Hongqiu; Han, Jing; Liu, Yulong (Frontiers in Public Health, 2025)
BackgroundRadiation literacy, encompassing the understanding of basic principles, applications, risks, and protective measures related to ionizing radiation, is critical for medical personnel working in jobs that involve the use of radioactive materials or medical imaging. In the context of nuclear emergency preparedness, the level of radiation knowledge among healthcare professionals—such as doctors, nurses, and radiographers—directly influences the effectiveness and safety of emergency responses. This study aims to address this gap by evaluating the radiation knowledge of medical personnel and identifying areas for improvement in profession-specific training programs.MethodsA cross-sectional study was conducted using a convenience sampling method. The study included 723 participants attending a medical emergency response exercise and clinical management workshop on radiation injury in Suzhou, China, in November 2023. Data were collected through a structured questionnaire, descriptive statistics and chi-square tests were performed to analyze participants’ radiation knowledge and identify variations across different professional groups.ResultsThe majority of participants were female (64.73%), married (75.10%), and held an undergraduate degree (69.99%). Nurses (40.11%) and clinical doctors (30.29%) constituted the largest professional groups. Significant disparities in radiation knowledge were observed among healthcare workers. Nurses and management personnel demonstrated a stronger grasp of fundamental radiation concepts, such as radioactive nuclides and absorbed doses, compared to clinical doctors. For instance, 85.52% of nursing personnel and 72.34% of management personnel accurately identified the half-life of iodine-131, while only 49.32% of clinical doctors showed comparable knowledge. Furthermore, substantial differences in radiation emergency response capabilities were noted across professions. These findings emphasize the necessity for tailored, profession-specific training programs in radiation protection and emergency preparedness.ConclusionThe study reveals a generally insufficient understanding of basic radiation concepts and emergency response principles among medical personnel. Significant variations in radiation knowledge were observed across different professional groups, highlighting the need for specialized training modules. These modules should focus on fundamental radiation concepts, radiation exposure effects, and emergency response protocols, with content customized to address the unique needs of each professional group. By implementing such targeted training, the overall effectiveness and safety of nuclear emergency responses can be significantly enhanced.